THE PERFORMANCE OPTIMIZATION OF THE BINTIBSOS UNIT TO PREVENT NARCOTICS ABUSE IN THE JURISDICTION OF POLRES BREBES - FATIR ALAM (Indonesian Journal of Police Studies, 2022)
This research is motivated by the increasing drug abuse in Brebes Regency. The strategic geographical location of Brebes Regency as a trade crossing is the key to the wheels of the economy on the island of Java, which is an attraction for foreign investors, including international network narcotics kingpins. The National Police as order is tasked with protecting, nurturing, serving the community, and enforcing the law through the Bintibsos Unit in preventing narcotics abuse from increasing. The problems that must be solved are the implementation of the Bintibsos unit performance through counseling to prevent narcotics abuse, efforts to improve the performance of the Bintibsos unit through counseling to prevent narcotics abuse . optimizing the performance of the Bintibsos unit in preventing narcotics cases in the jurisdiction of the Brebes Police. The research method used is descriptive qualitative method with an inductive approach. By collecting data through observation techniques, interviews, and document review, as well as validity and reliability by combining theory with existing concepts, data sources, and data collection techniques. The theories used in this research are Performance Theory, Management Theory, and Crime Prevention Theory. The concepts used are Optimization, Bintibsos Unit, Narcotics Abuse, Perpol No. 2 of 2021 and Perkap No. 21 of 2007. The results of research on the performance of Bintibsos personnel were analyzed through performance theory, which has been applied, but not yet optimal. Furthermore, the method used by Bintibsos is analyzed through management theory which can see the stages of planning, organizing, implementing and controlling that have not been carried out optimally because of the inhibiting factors, namely human resources, and performance methods. While the supporting factors are facilities and infrastructure, personnel loyalty, and cooperation with other units and units. Based on the results of the study, it is suggested that in order to optimize the performance of the Bintibsos unit, it is necessary to provide Binmas vocational education as well as counseling and coaching training, as well as providing innovation and creation in counseling and coaching methods.